The Geometry E-module Based on Numerical Literacy for the Fifth Grade of Elementary School - Dyah Triwahyuningtyas; Wahyu Meganingrum; Arnelia Dwi Yasa; Nyamik Rahayu Sesanti (IAIN Syekh Nurjati Cirebon, 2022)
AbstractAs a learning innovation, it is necessary to have e-module that brings an interesting learning atmosphere and increase student interests in learning mathematics. This research aims to develop a valid and practical geometry e-module based on numerical literacy for the fifth grade of elementary school. The method in development research uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Data were collected using validation questionnaires and student questionnaires. Data were then analyzed using descriptive qualitative and quantitative techniques. The results showed that the validator's assessment obtained the valid criteria, with a percentage of 99% (media experts), 83% (material experts), and 87% (linguists). In the practicality test, the teacher got 96% (excellent) and the students got 94% (excellent). Based on the assessment results, the geometry e-module based on numerical literacy for the fifth grade of elementary school has met the eligibility and practicality criteria. Therefore, teachers can use this e-module as a companion book in distance learning.Keywords: geometry, e-module, numerical literacy. AbstrakSebagai inovasi pembelajaran, perlu adanya e-modul yang membawa suasana pembelajaran yang menarik dan meningkatkan minat siswa dalam belajar matematika. Penelitian ini bertujuan untuk mengembangkan e-modul bangun ruang berbasis literasi numerasi untuk kelas 5 sekolah dasar yang valid dan praktis. Metode dalam penelitian pengembangan menggunakan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Data dikumpulkan dengan menggunakan kuesioner validasi dan angket siswa. Data kemudian dianalisis menggunakan teknik deskriptif kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa penilaian validator memperoleh kriteria valid dengan persentase 99% (ahli media), 83% (ahli materi), dan 87% (ahli bahasa). Pada uji kepraktisan, guru memperoleh 96% (sangat baik) dan peserta didik memperoleh 94% (sangat baik). Berdasarkan hasil penilaian tersebut, maka e-modul bangun ruang berbasis literasi numerasi untuk kelas 5 sekolah dasar dapat digunakan karena telah memenuhi kriteria kelayakan dan kepraktisan. Guru dapat menggunakan e-modul ini sebagai buku pendamping dalam pembelajaran jarak jauh.Kata kunci: bangun ruang, e-modul, literasi numerasi.